2022
DOI: 10.1111/1468-5973.12443
|View full text |Cite
|
Sign up to set email alerts
|

A social identity perspective on interoperability in the emergency services: Emergency responders' experiences of multiagency working during the COVID‐19 response in the UK

Abstract: Clifford (2022) A social identity perspective on interoperability in the emergency services: emergency responders' experiences of multi-agency working during the COVID-19 response in the UK. Journal of Contingencies and Crisis Management.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 52 publications
0
3
0
Order By: Relevance
“…Social identity theory (SIT) explains how people's group affiliations impact their attitudes, activities, and interactions [32]. In crisis scenarios, SIT suggests that people's group identification can influence their responses, including increased in-group cooperation and potential intergroup conflicts [48]. Understanding social identities allows for the identification and addressing of specific needs, challenges, and disparities faced by different social groups, ensuring more targeted and equitable crisis response efforts [34,35].…”
Section: Social Identity Perspectives In Collective Capabilities Duri...mentioning
confidence: 99%
See 1 more Smart Citation
“…Social identity theory (SIT) explains how people's group affiliations impact their attitudes, activities, and interactions [32]. In crisis scenarios, SIT suggests that people's group identification can influence their responses, including increased in-group cooperation and potential intergroup conflicts [48]. Understanding social identities allows for the identification and addressing of specific needs, challenges, and disparities faced by different social groups, ensuring more targeted and equitable crisis response efforts [34,35].…”
Section: Social Identity Perspectives In Collective Capabilities Duri...mentioning
confidence: 99%
“…Though not examined in the energy context, collective actions in crisis scenarios have been investigated in a) small-scale crisis scenarios, which pertain to local or regional events [35,48], and b) large-scale environmental crises [50]. In small-scale crisis scenarios, Davidson et al [48] explore the concept of shared social identity among local-level responders during the COVID-19 pandemic in the UK. He highlights the role of preexisting relations and a sense of shared common fate in facilitating collective activities.…”
Section: Social Identity Perspectives In Collective Capabilities Duri...mentioning
confidence: 99%
“…When characterizing interorganizational networks, prior studies have consistently identified numerous challenges in cross‐sector collaboration due to institutional disparities and differences in information systems (Lee et al, 2023; Nick et al, 2023; Wang et al, 2022). This ‘wall’ hampers information flow and diminishes the efficiency of interorganizational collaboration networks in emergency response (Davidson, 2023; Esteve et al, 2013). Building upon this understanding, scholars have investigated the antecedents of emergency management networks and examined the drivers behind their formation (McGuire & Silvia, 2010; Ramírez de la Cruz et al, 2020; Sapat et al, 2019; Zhang, Zou, et al, 2016).…”
Section: Introductionmentioning
confidence: 99%